2020
DOI: 10.3390/pharmaceutics13010014
|View full text |Cite
|
Sign up to set email alerts
|

Development of Processes for Recombinant L-Asparaginase II Production by Escherichia coli Bl21 (De3): From Shaker to Bioreactors

Abstract: Since 1961, L-asparaginase has been used to treat patients with acute lymphocytic leukemia. It rapidly depletes the plasma asparagine and deprives the blood cells of this circulating amino acid, essential for the metabolic cycles of cells. In the search for viable alternatives to produce L-asparaginase, this work aimed to produce this enzyme from Escherichia coli in a shaker and in a 3 L bioreactor. Three culture media were tested: defined, semi-defined and complex medium. L-asparaginase activity was quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
0
5
1
1
Order By: Relevance
“…Maximum volumetric enzyme activity values of 43,955 U/L and biomass of 69.90 g/L were obtained when induced with lactose. 36 Although the authors achieved a higher concentration of cells at the end of cultivation, when the yield is calculated using the ratio of maximum enzymatic activity per gram of cell produced, a value of 628.82 U/cell is obtained, almost 6-fold lower than the results obtained in this study. Mihooliya et al 37 expressed the L-asparaginase of Pseudomonas resinovorans in E. coli Rosetta (DE3), in a process conducted in a bioreactor with 1 L of working volume, during 24 h of experiment, with batch cultivation without feeding.…”
Section: Table 1 Results Of Kinetic Parameters Of Fed-batch Cultures ...contrasting
confidence: 79%
See 1 more Smart Citation
“…Maximum volumetric enzyme activity values of 43,955 U/L and biomass of 69.90 g/L were obtained when induced with lactose. 36 Although the authors achieved a higher concentration of cells at the end of cultivation, when the yield is calculated using the ratio of maximum enzymatic activity per gram of cell produced, a value of 628.82 U/cell is obtained, almost 6-fold lower than the results obtained in this study. Mihooliya et al 37 expressed the L-asparaginase of Pseudomonas resinovorans in E. coli Rosetta (DE3), in a process conducted in a bioreactor with 1 L of working volume, during 24 h of experiment, with batch cultivation without feeding.…”
Section: Table 1 Results Of Kinetic Parameters Of Fed-batch Cultures ...contrasting
confidence: 79%
“…The highest enzymatic activity obtained was approximately 98,000 U/L in the DO-stat controlled cultures (Figure B). This difference in yield observed between the strategies tested was probably due to the concentration of microbial cells, since an increase in the concentration of cells results in an increase in the production and activity of the recombinant enzyme, considering that it is expressed intracellularly. , The condition that showed the highest biomass and enzyme activity was DO-stat with induction in 18 h (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…There are few studies addressing the influence of inducer (lactose or IPTG) concentration on recombinant protein production by conventional E. coli BL21(DE3) cells under lac operon control (Einsfeldt et al 2011 ; Lecina et al 2013 ; Ferreira et al 2018 ; Barros et al 2021 ; Von den Eichen et al 2021 ), but none for ClearColi® BL21(DE3) so far. Segovia-Trinidad et al ( 2021 ) reported that other induction methods and inducer concentrations did not increase soluble production of constitutive-active human-Smad8, but they did not detail their investigation nor present the results.…”
Section: Discussionmentioning
confidence: 99%
“…L-ASNase was synthesized in a shaker and then scaled up to a bioreactor, resulting in a 27-fold increase in cell concentration and enzyme yield. When the cell concentration was scaled up to the bioreactor, it increased 27-fold, reaching approximately 70 g/L dry weight and 43,954.79 U/L volumetric activity [142].…”
Section: Optimization Of L-asparaginase Production In Escherichia Colimentioning
confidence: 99%